Modernity in a Colonial Landscape: Hotel Kalitaman Salatiga 1930-1950 - Marinda, Dina Nanda; Wijayati, Putri Agus (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This study examines the Kalitaman Hotel in Salatiga as one of the representations of colonial modernity in a small town. Through historical methods, including heuristics, verification, interpretation, and historiography, this study successfully presents a historical narrative that a building, such as a hotel, not only functions as a place to stay, but also as a symbol of colonial modernity in terms of architecture and socio-cultural functions. The Kalitaman Hotel was built in a tropical architectural style that adapts to the local climate, but still reflects a European style. This is because Salatiga is a city that is used as one of the residences for Dutch citizens who visit or settle in central Java. In addition, this hotel became an important socio-political and cultural meeting space, both for colonial and local elites. Activities such as dance parties, bridge competitions, and visits by important figures show that this hotel became a meeting point between the social networks of the Dutch East Indies and the local conditions of Salatiga. After independence, the function of the hotel underwent a transformation but remained a strategic social space. This study shows that colonial modernity was not only centered in big cities, but also had a strong influence on small towns like Salatiga.